Δ1‐pyrroline‐5‐carboxylate reductase from Arabidopsis thaliana: stimulation or inhibition by chloride ions and feedback regulation by proline depend on whether NADPH or NADH acts as co‐substrate. Issue 3 (28th January 2014) - Giberti, Samuele; Funck, Dietmar; Forlani, Giuseppe
Summary: Δ 1 ‐pyrroline‐5‐carboxylate (P5C) reductase (P5CR) catalyses the final step of proline synthesis in plants. In Arabidopsis thaliana, protein levels are correlated neither to the corresponding mRNA copy numbers, nor to intracellular proline concentrations. The occurrence of post‐translational regulatory mechanisms has therefore been hypothesized, but never assessed. The purification of A. thaliana P5CR was achieved through either a six‐step protocol from cultured cells, or heterologous expression of AtP5CR in Escherichia coli . The protein was characterized with respect to structural, kinetic, and biochemical properties. P5CR was able to use either NADPH or NADH as the electron donor, with contrasting affinities and maximum reaction rates. The presence of equimolar concentrations of NADP + completely suppressed the NADH‐dependent activity, whereas the NADPH‐dependent reaction was mildly affected. Proline inhibited only the NADH‐dependent reaction. At physiological values, increasing concentrations of salt progressively inhibited the NADH‐dependent activity, but were stimulatory of the NADPH‐dependent reaction. The biochemical properties of A. thaliana P5CR suggest a complex regulation of enzyme activity by the redox status of the pyridine nucleotide pools, and the concentrations of proline and chloride in the cytosol. Data support a to date underestimated role of P5CR in controlling stress‐induced proline accumulation.